Floristic examination of diatom assemblage in the dim light-environment of water column and sea ice, Saroma Ko lagoon, Hokkaido, Japan - Ikeya, Tohru; Kikuchi-Kawanobe, Kyoko; Kudoh, Sakae (National Institute of Polar Research, 2001)
P(論文) The species composition and abundance of diatoms were examined concurrently in both the sea ice and the water column of ice-covered Saroma Ko lagoon in early February 1996. Cell counts indicated that the ice algal assemblage collected from the bottom 10cm of the sea ice was dominated by Detonula confervacea, Thalassiosira spp. and Fragilariopsis cylindrus in order of total cell volume. These three groups accounted for 66% of the total diatom abundance in the sea ice. The centric and pennate diatoms accounted for 52.3% and 47.7% of the abundance of the ice algal assemblage, respectively. The phytoplankton assemblage collected from the water column at the depth of 4m was dominated by Thalassiosira spp., T. nordenskioeldii and D. confervacea. These three groups accounted for 92% of the total phytoplankton diatom abundance. The centric diatoms accounted for as much as 98.8% of the abundance of the phytoplankton assemblage whereas the pennate diatoms accounted for only 1.2%. Two of the three dominant phytoplankton groups were observed in both the ice algal and phytoplankton assemblages, but T. nordenskioeldii was present only in the latter. The groups observed only in the phytoplankton assemblage accounted for 20% of the total phytoplankton abundance. It was assumed that the phytoplankton assemblage included some species released from the sea ice and others living independently in the water column where light was severely limited. In response to the improvement of the light-environment, those cells surviving in the water column during winter can resume growth soon after the disappearance of the sea ice cover. departmental bulletin paper